THE IMPROVEMENT OF THE STUDENTS’ SPEAKING PROFICIENCY THROUGH PLUS, MINUS, INTERESTING (PMI) STRATEGY - Azis, Awalia (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
This research aimed to find out whether through Plus, Minus, Interesting (PMI) Strategy (An Experimental Study at the Second Grade of SMA Datuk Ribandang Makassar) can improve the students’ speaking proficiency in terms speaking accuracy dealing with pronunciation and  fluency dealing with smoothness. A pre-experimental design was employed with one class of the second grade in SMA Datuk Ribandang Makassar, selected purposively as sample. The data obtained through a pre-test and post-test in speaking test. The research results indicated that the use of Plus, Minus, Interesting (PMI) Strategy could improve the students’ accuracy and fluency in speking proficiency especially in pronunciation, vocabulary and smoothness. It was proved by the students’ mean score of pre-test was (5.28) and in post-test was (7.62). The findings of this research shows that the value of t-test in the posttest is higher than t table (4.29 > 2.09). It means that there was significant difference of the students’ pronunciation and smoothness in speaking English before and after being taught using Plus, Minus, Interesting (PMI) Strategy at the Second Grade of SMA Datuk Ribandang. The statistical computation showed that Plus, Minus, Interesting (PMI) Strategy was effective in improving the students’ speaking proficiency in accuracy and fluency.